Social Criticism in The Novel “Teruslah Bodoh, Jangan Pintar” by Tere Liye (Sociological Study of Literature) - Ramadani Khusnul Khotimah1; Haris Supratno (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze social criticism in the novel